Exploring the Benefits and Challenges of Artificial Intelligence (AI) in Nursing - Cyril B. Romero; Oscar Agyemang Opoku; Sitti Syabariyah; Dhesi Ari Astuti; Iqra Asif; Rostinah (Engineering Science Letter, 2023)
This paper discusses the trend of AI (Artificial Intelligence) and its role in the healthcare industry. AI is being used to improve efficiency and effectiveness in healthcare. Still, challenges remain, such as privacy and data protection and healthcare workers' hesitancy to replace their work with technology. This study aims to see opportunities for using AI in the health sector and understand existing problems, such as barriers to significant initial investments. This study uses a qualitative approach and focuses on the author's understanding based on secondary sources and personal experience. The study results show that AI can assist health workers in making diagnoses and providing more efficient health services. However, it still has to be used as a tool and cannot replace the role of health workers as a whole.